(untitled) (The Research of Medical Science Review, 2025)
Breastfeeding is explained as nourishing the baby or young child with breast milk, which includes expressed milk or from wet nurse. It is very important to ensure the healthy upbringing and reduction of infant death by ensuring child feeding practices. It is recommended by The World Health Organization (WHO) and United Nations International Children's Emergency Fund (UNICEF) to exclusively breastfeed (EBF) the babies for the first six months of life. It is important for the health of babies as well as mothers. The study designed to assess the factors influencing breastfeeding practices in working mothers of Muzaffarabad, Azad Jammu and Kashmir, is a cross-sectional study. A total of 100 working women of different professions from both public and private setup of city Muzaffarabad AJK were interviewed by using pre- structured self-administered questionnaire. The questions were asked about socio- demographic information of working mothers, formula initiation, current feeding practices, available workplace breastfeeding support and workplace barriersthat are in turn affecting their breastfeeding practices. Results showed suboptimal breastfeeding practices among working women. None of the mothers followed exclusive six-month postpartum breastfeeding. The majority (57%) initiated formula feed from 1 month to 3 months age. Returning to work was strongly associated with cessation of breastfeeding (59%) and use of supplemental feedings. Majority of workplaces were lacking in provision of flexible time for breastfeeding (6/100), task adjustment during lactation period (6/100), separate room for breastfeeding (32/100), nursery for childcare (3/100), breast pump to express breast milk (17/100) and refrigerator to store expressed milk (0/100).